PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA TOKO MONTE SWALAYAN CAFÉ SALON DI KOTA PALOPO : Study Kasus Swalayan (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to analyze the effect of service quality and price on customer satisfaction at monte self-service café salon shops (self-service case study) in Palopo City. Sampling method with incidental sampling (incidental sampling). The number of samples in this study were 33 respondents from an unknown population. Data collection techniques using observation, questionnaire and documentation. Data processing techniques with a regression system with the help of SPSS software (Statistical Package for the Social Sciences) data analysis techniques used are validity test, reliability test, multiple linear regression test, determinant coefficient test, t test (partial) and F test (simultaneous) . The results of this study concluded that service quality has a positive and significant impact on consumer satisfaction at Monte Self-Service Stores in Palopo City. There is an effect of price on consumer satisfaction, the better the quality of service and the price provided, the more satisfied consumers will feel, the more positive and significant effect this will have on consumer satisfaction at monte supermarkets in the city of Palopo.